2021
DOI: 10.3390/ijms22136793
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Compounds (QACs) and Ionic Liquids (ILs) as Biocides: From Simple Antiseptics to Tunable Antimicrobials

Abstract: Quaternary ammonium compounds (QACs) belong to a well-known class of cationic biocides with a broad spectrum of antimicrobial activity. They are used as essential components in surfactants, personal hygiene products, cosmetics, softeners, dyes, biological dyes, antiseptics, and disinfectants. Simple but varied in their structure, QACs are divided into several subclasses: Mono-, bis-, multi-, and poly-derivatives. Since the beginning of the 20th century, a significant amount of work has been dedicated to the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 187 publications
4
109
0
Order By: Relevance
“…QACs are a well-known class of cationic biocides with a broad spectrum of antimicrobial activity. QACs kill bacteria by impairing the permeability of cell membranes and do not contribute to antimicrobial resistance [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…QACs are a well-known class of cationic biocides with a broad spectrum of antimicrobial activity. QACs kill bacteria by impairing the permeability of cell membranes and do not contribute to antimicrobial resistance [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microbiocides, in terms of chemicals, are classified as oxidizing substances, alcohols, phenols and their derivatives, aldehydes, organic and inorganic acids, halogen compounds, and quaternary ammonium compounds [ 7 , 8 , 9 ]. They are used as antiseptics, disinfectants, and preservatives in a wide variety of fields: water purification, personal care products, food and beverage, wood preservation, paints and coatings, plastics, cleaning products, ventilation and air conditioning, medical products, and also in oil, gas, fuel, and paper industry [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they have been extensively applied in the fields of antibacterial and antitumor materials [ 10 , 11 , 12 ]. For example, some review articles have summarized the relationship between the antibacterial properties of quaternary ammonium salts and its structure [ 13 , 14 , 15 ]. Furthermore, Linda et al developed a series of quaternary ammonium compounds (QACs) derived from quinuclidin-3-ol and an alkyl chain of variable length, and found that it is necessary for new compounds to get better antimicrobial potentials by the addition of alkyl chains containing at least ten carbon atoms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%